Pakan Sapi Simental Jantan di Taman Ternak Ruminansia Maron, Kabupaten Temanggung, JawaTengah: Male Simental Cow Feed at Ruminansia Maron Cattle Park, Temanggung Regency, Central Java - Setiawan, Beni Pratama; Arifin, Hanung Dhidhik (Jurnal Riset Agribisnis dan Peternakan, 2024)
Simental cows are superior cows crossed between German cattle and Swiss cattle. An important issue in superior cattle is the need for feed. The purpose of this study is the feed needs of male simental beef cattle. The research material is 16 male simental cows with a weight of 200-250 kg. The parameters observed were the amount of feed, feed consumption, drinking water consumption, weight gain, conversion and distribution of feed. The parameters are measured based on the consumption of dry materials. The average feed given is 22.06 kg / day. and concentrate 2.21 kg /day. with a weight of 219.19 kg. The drinking water provided is 17.06 liters/day. Feed consumption was 2.82 % (BK) with TDN 66.40 %, Pk 14.40 %,. Daily weight gain of 1.24. Feed conversion is 5.09% and efficiency is 19.65%. The conclusion that the feed given in the form of forage and concentrate has a fairly high PBBH.